A study of plot ratio/building height restrictions in high density cities using 3D spatial analysis technology: A case in Hong Kong. (July 2017) - Guo, Jian; Sun, Bingxia; Qin, Zhe; Wong, Siu Wai; Wong, Man Sing; Yeung, Chi Wai; Shen, Qiping
Abstract: Hong Kong is an international metropolis with a highly dense population. As a result, it faces enormous challenges in terms of land supply. As part of the Hong Kong Government's initiative to increase land supply, the Civil Engineering and Development Department (CEDD) proposed minor relaxation of the maximum plot ratio/building height restrictions for 21 target sites in Kai Tak Development Area (KTDA). Although CEDD has explored the feasibility of increasing development intensity by assessing environmental impacts, infrastructure capacity and public consultation, these reviews and assessments were conducted based on the 2D GIS. Since the spatial distribution of land unit in the real world is three-dimensional, 3D GIS can help us look into the world in true perspective and make informed decisions. This study aims to investigate the viability of minor relaxation of maximum plot ratio/building height restrictions of 21 sites in KTDA through 3D modeling and 3D spatial analyses, including skyline, visual impact, shadow and solar exposure. Regarding to the 21 target sites, four scenarios with different plot ratios and building heights were built and compared. The results indicate that minor relaxation of maximum plot ratio and building height leads to (i) minor effect on skyline (ii) minor effect on visual impact and (iii) slight changes in shadow and solar exposure both in winter and summer. Therefore, in light of the findings from this study, scenario 4 is the recommended reasonable scale to relax the maximum plot ratio/building height restriction for the target sites in KTDA. Besides, this study can also be applied in the urban renewal studies and other new development areas in Hong Kong, or even in other densely populated cities. Highlights: 3D models of Kai Tak and surrounding areas were established. Various 3D spatial analyses of different plot ratio/building height scenarios were conducted. The minor relaxation of plot ratio and building height leads to minor effect on skyline, visual impact and solar exposure. The proposed method can also be applied in urban studies in other similar densely populated cities.